Relativistic Calculation of Hyperfine Parameters of Mercury Compounds - Filatov, Michael; Zou, Wenli; Cremer, Dieter (Current Inorganic Chemistry (Discontinued), 2013)
The normalized elimination of the small component (NESC) method is a Dirac-exact relativistic method that leads to reliable first order response properties such as contact densities, Mössbauer shifts, electric field gradients, quadrupole coupling constants, or hyperfine structure constants for heavy atoms. In this review, the calculation of these hyperfine parameters with a NESC analytical derivatives formalism is discussed and demonstrated for mercury containing molecules. There is a distinct need for accurate calculated hyperfine parameters because the possibilities of experiment are limited in a case such as mercury. This need can be fulfilled if, beside scalar relativistic effects, the influence of spin-orbit coupling, electron correlation and the finite dimension of the nucleus are accounted for.
Keywords: quadrupole coupling constant